2004
DOI: 10.1023/b:bege.0000038493.26202.d3
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping Pooled DNA on Microarrays: A Systematic Genome Screen of Thousands of SNPs in Large Samples to Detect QTLs for Complex Traits

Abstract: Large samples and systematic screens of thousands of DNA markers are needed to detect quantitative trait loci (QTLs) of small effect size. One approach to conduct systematic genome scans for association is to use microarrays which, although expensive and non-reusable, simultaneously genotype thousands of single-nucleotide polymorphisms (SNPs). This brief report provides proof of principle that groups of pooled DNA (for example cases and controls) can be genotyped reliably on a microarray. DNA was pooled for 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 26 publications
2
88
0
Order By: Relevance
“…DNA was extracted from buccal swabs 44 and DNA pools constructed as described in our previous publications. [29][30][31]34 Briefly, each sample was quantified using a spectrophotometer (260 nm) and diluted to a target concentration of 50 ng/ml. Each sample was then quantified once by fluorimetry (employing PicoGreen dsDNA quantitation reagent; Invitrogen, Molecular Probes, CA, USA) before being diluted further to 25 ng/ml and quantified in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA was extracted from buccal swabs 44 and DNA pools constructed as described in our previous publications. [29][30][31]34 Briefly, each sample was quantified using a spectrophotometer (260 nm) and diluted to a target concentration of 50 ng/ml. Each sample was then quantified once by fluorimetry (employing PicoGreen dsDNA quantitation reagent; Invitrogen, Molecular Probes, CA, USA) before being diluted further to 25 ng/ml and quantified in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Pooled DNA can be allelotyped reliably on microarrays. [29][30][31][32][33] We have used the SNP-MaP method with a 10K microarray to identify QTLs associated with mild mental impairment in a multistage design that includes confirmation by individual genotyping of SNPs nominated in the SNP-MaP scan. 34 In the present study, we apply the SNP-MaP method using 100K SNP microarrays in a three-stage QTL association scan of early reading disability and ability in a representative UK sample of 5760 7-yearold children assessed on two measures of reading that we have shown to be highly heritable and highly genetically correlated 6,7 In the first stage we used pooled DNA to screen for the largest SNP allele frequency differences for more than 100 000 SNPs comparing low (N = 755) and high (N = 747) reading groups.…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, we have successfully used pooled DNA on the Affymetrix GeneChip s Mapping 10 K array Xba 131. 37 Although these microarrays do not focus on functional polymorphisms, over 40% of the SNPs on the microarray are within the 2% of DNA that encompasses genes and thus provide sufficiently dense markers of genes for systematic screens for indirect association.…”
Section: Nonsynonymous Snpsmentioning
confidence: 99%
“…While DNA pooling offers a substantial reduction in genotyping cost, it possesses some disadvantages, primarily in the loss of information (genotype and haplotype distributions) and by introducing estimation errors. Recent studies have shown the feasibility and accuracy of estimating single-nucleotide polymorphism (SNP) allele frequencies in DNA pools using microarrays containing thousands of SNPs, [19][20][21][22][23] which makes it possible to perform whole genome association studies in a cost-effective way.…”
Section: Introductionmentioning
confidence: 99%